Ohio boundary no. 2 : Map exhibiting the positions occupied on the Maumee Bay and river: viz: Turtle Island, the North Cape, and that above Toledo, together with the position of the "east line," in its passage of the Maumee River surveyed under the direction of Capt. Talcott, U.S. Engineers, by Lieuts. Hood & R.E. Lee / drawn by Lieut. Jas. R. Irwin, U.S. Army 1835. - Irwin, James R., d. 1848. (William L. Clements Library Image Bank, 1835)
Removed from: Ohio and Michigan boundary ., 1836.; Endorsed at lower right: A. Talcott capt engs.